HIV Viral Dynamic under Treatment with Intracellular Delay and Virus Decay as Interactive Parameters - C. Prata, R. A.; M. Jafelice, R. S.; M. Cabral, V.; S. Pedro, F.; C. Barros, L. (Trends in Computational and Applied Mathematics, 2021)
Treatment with antiviral drugs for human immunodeficiency virus type 1 (HIV-1) infection causes a rapid reduction in plasma viral load. Viral decline occurs in several stages and provides information on important kinetic constants of virus replication in vivo and pharmacodynamic properties. We present a mathematical model that not only considers the intracellular phase of the viral life cycle, defined as the time between the infection of a cell and the production of new viral particles, but we  also consider that this parameter together with the virus decay are interactive fuzzy numbers.